ASSISTANCE IN THE UTILIZATION OF STORY-TELLING BOOK OF CHARACTER BUILDING FOR TEACHERS IN PAUD SURYA GEMILANG, MALANG - Kharisma Sabgini; Triastama Wiraatmaja; Agista Nidya Wardani (Premise: Journal of English Education and Applied Linguistics, 2021)
The aims of this study are: 1) to find out how the teacher training in PAUD Surya Gemilang, Malang, is carried out in implementing the book Let’s Respect Each Other: A Story-Telling Book of Character Building by using various methods and fun learning techniques, and 2) how the practice of using the book of Let’s Respect Each Other: A Story-Telling Book of Character Building. This research was conducted using a qualitative method in which the researcher described the process of the two aims aforementioned. The subjects of this study were all teachers, especially one homeroom teacher at PAUD Surya Gemilang. The results of this study found that in the first phase, namely teacher training, there were three stages. They were the provision of English for Young Learners material, the provision of story-telling material, and the provision of character education material. Then, in the second phase, namely the implementation of Let’s Respect Each Other: A Story-Telling Book of Character Building, it was found that teachers taught stories and character education by reading books in English and Bahasa alternately while showing the pictures that matched the story to students and retelling the stories by using puppets.